Spectrophotometric Determination of Leflunomide in Bulk and Pharmaceutical Formulations - SRINU BABU, G.; SARAT BABU, I.; KIRAN KUMAR, N.; YUGANDHAR, N.M.; A.I. RAJU, CH. (Asian Journal of Chemistry, 2010)
A simple, sensitive and precise spectrphotometric methods have been developed for the estimation leflunomide in bulk and dosage forms. Methanol was used as solvent for the estimation of the entire drug 2 with apparent molar absorbitivity of 55277 L mol-1 cm-1. Beer’s law was obeyed in the concentration range of 2-30 μg/mL. Results of the analysis were validated statistically and by recovery studies.